2021
DOI: 10.34172/jlms.2021.25
|View full text |Cite
|
Sign up to set email alerts
|

Dosage Effects of an 810 nm Diode Laser on the Proliferation and Growth Factor Expression of Human Gingival Fibroblasts

Abstract: Introduction: A substantial amount of evidence supports the positive effect of photobiomodulation on the proliferation and differentiation of various cell types. Several laser wavelengths have been used for wound healing improvement, and their actual outcome depends on the settings utilized during irradiation. However, the heterogeneous wavelengths and laser settings applied in the existing literature make it difficult to draw solid conclusions and comparison of different studies. The aim of the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…The therapeutic potential of LLLT could be attributed to its inductive effect for the secretion of endogenous opioids, increasing vasodilatation, stimulating tissue regeneration, and reducing inflammation through the reduction of prostaglandin E2 and cyclo-oxygenase 2 (COX-2) release, 20 as well as decreasing reactive oxygen species (ROS) levels, mRNA expression of phospholipase A2 and TNF-α levels allowing LLLT to be a good alternative to NSAIDs avoiding any possible drugs' side effects. 21 In a study conducted by Karoussis et al, 22 LLLT was found to enhance the expression of epidermal growth factor (EGF), transforming growth factor (TGF), and vascular endothelial growth factor (VEGF) as well as stimulating collagen production and cellular proliferation in human fibroblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of LLLT could be attributed to its inductive effect for the secretion of endogenous opioids, increasing vasodilatation, stimulating tissue regeneration, and reducing inflammation through the reduction of prostaglandin E2 and cyclo-oxygenase 2 (COX-2) release, 20 as well as decreasing reactive oxygen species (ROS) levels, mRNA expression of phospholipase A2 and TNF-α levels allowing LLLT to be a good alternative to NSAIDs avoiding any possible drugs' side effects. 21 In a study conducted by Karoussis et al, 22 LLLT was found to enhance the expression of epidermal growth factor (EGF), transforming growth factor (TGF), and vascular endothelial growth factor (VEGF) as well as stimulating collagen production and cellular proliferation in human fibroblast cells.…”
Section: Discussionmentioning
confidence: 99%